Recovery of defects from the information at detectors. (4th April 2016) - Kutsenko, Anton A
Abstract: A discrete wave equation in a multidimensional uniform space with local defects and sources is considered. The characterization of all possible defect configurations corresponding to given amplitudes of waves at the receivers (detectors) is provided.